2020
DOI: 10.1007/s11920-020-01166-z
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of Epidemic and Pandemic Outbreaks on Healthcare Workers: Rapid Review of the Evidence

Abstract: Purpose of Review We aim to provide quantitative evidence on the psychological impact of epidemic/pandemic outbreaks (i.e., SARS, MERS, COVID-19, ebola, and influenza A) on healthcare workers (HCWs). Recent Findings Forty-four studies are included in this review. Between 11 and 73.4% of HCWs, mainly including physicians, nurses, and auxiliary staff, reported post-traumatic stress symptoms during outbreaks, with symptoms lasting after 1-3 years in 10-40%. Depressive symptoms are reported in 27.5-50.7%, insomnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

57
658
6
54

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(775 citation statements)
references
References 55 publications
57
658
6
54
Order By: Relevance
“…Although psychological symptoms have been found to be particularly high among those working on the frontline during the pandemic [ 5 , 6 , 7 , 8 ], non-frontline heath care workers have also reported such symptoms [ 9 ]. Moreover, these symptoms have been more severe among females and younger workers [ 4 , 10 , 11 ], as well as for those with prior mental health problems [ 12 , 13 ]. In addition to these cases, social sector workers, who have seldom been acknowledged in the recent COVID-19 literature, have also faced risk of infection in their work [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although psychological symptoms have been found to be particularly high among those working on the frontline during the pandemic [ 5 , 6 , 7 , 8 ], non-frontline heath care workers have also reported such symptoms [ 9 ]. Moreover, these symptoms have been more severe among females and younger workers [ 4 , 10 , 11 ], as well as for those with prior mental health problems [ 12 , 13 ]. In addition to these cases, social sector workers, who have seldom been acknowledged in the recent COVID-19 literature, have also faced risk of infection in their work [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among health care and social sector workers, the perceived infection risk is dependent on the protective measures taken by organizational infrastructures and governments. Accordingly, confidence in protective measures has been found to be associated with reduced psychological symptoms [ 13 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-traumatic stress symptoms were reported by 11%–73% of HCP during epidemic or pandemic outbreaks that lasted in up to 10–40% after 1–3 years ( Preti et al;, 2020 ).…”
Section: Mental Health Impact On Frontline Healthcare Professionals (mentioning
confidence: 99%
“…As such, previous research concerning the current pandemic revealed heightened stress among individuals due to fear of infection, transmitting the virus to the loved ones, lack of information and boredom, and loss of social communication (Zandifar & Badrfam, 2020;Zhang et al, 2020). In support, several studies documented that perceived stress is an important concept to investigate during the pandemic (Du et al, 2020;McAlonan et al, 2007;Mo et al, 2020;Preti et al, 2020) and might be impactful on developing depression symptoms (e.g., Gotlib et al, 2020;Montano & Acebes, 2020) .…”
Section: Introductionmentioning
confidence: 97%